Specific Thiazolidinediones Inhibit Ovarian Cancer Cell Line Proliferation and Cause Cell Cycle Arrest in a PPARγ Independent Manner - Al-Alem, Linah; Southard, R. Chase; Kilgore, Michael W.; Curry, Thomas E. (PLOS ONE, 2011)
Background Peroxisome Proliferator Activated Receptor gamma (PPARγ) agonists, such as the thiazolinediones (TZDs), have been studied for their potential use as cancer therapeutic agents. We investigated the effect of four TZDs—Rosiglitazone (Rosi), Ciglitazone (CGZ), Troglitazone (TGZ), and Pioglitazone (Pio)—on ovarian cancer cell proliferation, PPARγ expression and PPAR luciferase reporter activity. We explored whether TZDs act in a PPARγ dependent or independent manner by utilizing molecular approaches to inhibit or overexpress PPARγ activity. Principal Findings Treatment with CGZ or TGZ for 24 hours decreased proliferation in three ovarian cancer cell lines, Ovcar3, CaOv3, and Skov3, whereas Rosi and Pio had no effect. This decrease in Ovcar3 cell proliferation was due to a higher fraction of cells in the G0/G1 stage of the cell cycle. CGZ and TGZ treatment increased apoptosis after 4 hours of treatment but not after 8 or 12 hours. Treatment with TGZ or CGZ increased PPARγ mRNA expression in Ovcar3 cells; however, protein levels were unchanged. Surprisingly, luciferase promoter assays revealed that none of the TZDs increased PPARγ activity. Overexpression of wild type PPARγ increased reporter activity. This was further augmented by TGZ, Rosi, and Pio indicating that these cells have the endogenous capacity to mediate PPARγ transactivation. To determine whether PPARγ mediates the TZD-induced decrease in proliferation, cells were treated with CGZ or TGZ in the absence or presence of a dominant negative (DN) or wild type overexpression PPARγ construct. Neither vector changed the TZD-mediated cell proliferation suggesting this effect of TZDs on ovarian cancer cells may be PPARγ independent. Conclusions CGZ and TGZ cause a decrease in ovarian cancer cell proliferation that is PPARγ independent. This concept is supported by the finding that a DN or overexpression of the wild type PPARγ did not affect the changes in cell proliferation and cell cycle.